Study of the Effect of Movable Water Saturation on Gas Production in Tight Sandstone Gas Reservoirs - Jie Zhang; Xizhe Li; Weijun Shen; Shusheng Gao; Huaxun Liu; Liyou Ye; Feifei Fang (Energies, 2020)
The movable water saturation of tight sandstone reservoirs is an important parameter in characterizing water production capacity, and there is a great need to understand the relationship between movable water saturation and water production characteristics. However, movable water behavior in this context remains unclear. In this study, four groups of tight sandstone cores from the Sulige gas field are measured to understand the movable water saturation characteristics. Then, the effects such as reservoir micropore throat, clay mineral and physical properties on movable water saturation are analyzed, and the movable water saturation and water production characteristics are discussed. The results show that higher movable water saturation will result in a greater amount of water in the gas drive. There is a critical pressure difference of the gas drive, and a large amount of movable water will flow out. Movable water saturation is independent of the porosity, permeability and initial water saturation, while it is closely related to the reservoir micropore throat and clay mineral content. Movable water is mainly distributed in the medium and large pores; the larger the proportion of such pores, the higher the degree of movable water saturation. A lower mineral content will lead to higher movable water saturation in tight sandstone gas reservoirs. These results provide clues for identifying gas–water bearing reservoirs and evaluating and predicting the water production characteristics in gas wells in tight sandstone gas reservoirs.